The longitudinal relationship between community programmes and policies to prevent childhood obesity and BMI in children: the Healthy Communities Study. (28th February 2018) - Strauss, W. J.; Nagaraja, J.; Landgraf, A. J.; Arteaga, S. S.; Fawcett, S. B.; Ritchie, L. D.; John, L. V.; Gregoriou, M.; Frongillo, E. A.; Loria, C. M.; Weber, S. A.; Collie‐Akers, V. L.; et al.
Summary: Background: Although a national epidemic of childhood obesity is apparent, how community‐based programmes and policies (CPPs) affect this outcome is not well understood. Objectives: This study examined the longitudinal relationship between the intensity of CPPs in 130 communities over 10 years and body mass index (BMI) of resident children. We also examined whether these relationships differ by key family or community characteristics. Methods: Five thousand one hundred thirty‐eight children in grades K‐8 were recruited through 436 schools located within 130 diverse US communities. Measures of height, weight, nutrition, physical activity and behavioural and demographic family characteristics were obtained during in‐home visits. A subsample of families consented to medical record review; these weight and height measures were used to calculate BMI over time for 3227 children. A total of 9681 CPPs were reported during structured interviews of 1421 community key informants, and used to calculate a time series of CPP intensity scores within each community over the previous decade. Linear mixed effect models were used to assess longitudinal relationships between childhood BMI and CPP intensity. Results: An average BMI difference of 1.4 kg/m 2 ( p ‐value < 0.01) was observed between communities with the highest and lowest observed CPP intensity scores, after adjusting for community and child level covariates. BMI/CPP relationships differed significantly by child grade, race/ethnicity, family income and parental education; as well as community‐level race/ethnicity. Conclusions: These results indicate that, over time, more intense CPP interventions are related to lower childhood BMI, and that there are disparities in this association by sociodemographic characteristics of families and communities. Abstract : This article is part of the upcoming supplement: The Healthy Communities Study: Examining Community Programs, Policies and Other Characteristics in Relation to Child Weight, Diet, and Physical Activity.